Do views of offshore wind energy detract? A hedonic price analysis of the Block Island wind farm in Rhode Island. (August 2022) - Dong, Luran; Lang, Corey
Abstract: Social concern and disapproval of offshore wind by coastal communities causes delays and costs to offshore wind development. One concern is property value impacts stemming from a loss of pristine ocean views. We evaluate this concern using the Block Island Wind Farm (BIWF), the first of its kind in the United States. While the BIWF has fewer turbines than currently proposed offshore wind developments, it is situated about 26 km [16 miles] from the Rhode Island mainland, which is a policy relevant distance, given that proposed US developments tend to be 21–32 km from coastlines. Using properties from the mainland, we estimate difference-in-differences hedonic valuation models with treatment defined by views of BIWF. Across many specifications and samples, we find no evidence of negative impacts to property values. Coefficient estimates are both negative and positive, but none are statistically distinguishable from zero. We additionally estimate hedonic models using properties on Block Island, which is only 4.8 km from the BIWF, meaning the BIWF is more of a visually dominant feature there as compared to the mainland. These models similarly find insignificant effects of views. In sum, our findings suggest that the viewshed impacts of the BIWF were minimal. Highlights: We study property value impacts of views of Block Island offshore wind farm. We use dif-in-dif method to examine valuation of views from mainland Rhode Island. Results suggest no adverse impact of offshore wind views.